1987
DOI: 10.1103/physrevb.35.5761
|View full text |Cite
|
Sign up to set email alerts
|

Valence-band photoemission inUO2(111) near the5dresonant photon energy

Abstract: Pronounced Fano-like resonant effects are observed in the photoemission spectra of the localized U 5f and 02p -U 5f, 6d bonding bands of U02 when photon energies near the U 5d3/2 $/2 thresholds (105 and 97.1 eV, respectively) are employed. The constant-final-state spectra are well hv described by calculated transition energies and oscillator strengths for the 5d' Sf '~5d 5f ' process;also, the decay rates of the intermediate-state multiplets are in qualitative agreement with the observed width of the spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 18 publications
12
29
0
Order By: Relevance
“…The calculation suggests that the U formal oxidation state is +4 with two unpaired 5f electrons. The calculated density of states shows that at the top of the valence band is mainly U-5f band, and the O-2p band is $3-6 eV below the Fermi level, consistent with the result from photoemission spectroscopic experiments [57]. The calculated unit cell constant is 5.54 Å with the GGA+U (U = 3.8, J = 0.4) methods, $1% higher than 5.47 Å of an experimental value at ambient temperature [58].…”
Section: Dft+u Description Of Uo 2+xsupporting
confidence: 86%
“…The calculation suggests that the U formal oxidation state is +4 with two unpaired 5f electrons. The calculated density of states shows that at the top of the valence band is mainly U-5f band, and the O-2p band is $3-6 eV below the Fermi level, consistent with the result from photoemission spectroscopic experiments [57]. The calculated unit cell constant is 5.54 Å with the GGA+U (U = 3.8, J = 0.4) methods, $1% higher than 5.47 Å of an experimental value at ambient temperature [58].…”
Section: Dft+u Description Of Uo 2+xsupporting
confidence: 86%
“…3). Previously, Cox et al [15] observed only a change in the intensity of the spectrum of OVMO electrons at electron binding energies from 0 to 13 eV. In [8], we observed for the first time the resonance in the spectra of UO 2 and ThO 2 for OVMO and IVMO electrons at electron binding energies within 0340 eV (Fig.…”
Section: Conversion Electron Spectroscopy (Ces)mentioning
confidence: 57%
“…Resonance photoemission based on 5d-5f Fano resonance revealed the 5f nature of this feature. 50 Dispersion in the O 2p manifold between 24 and 28 eV was also observed. 12 Here we report dispersion in the dominant 5f feature.…”
mentioning
confidence: 71%